Empirical Evidence on the Effectiveness of Social Public Procurement Policy: The Case of the Swiss Apprenticeship Training System - Mirjam Strupler Leiser; Stefan C. Wolter (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper assesses the effectiveness of a social public procurement policy in Switzerland that gives firms that train apprentices' a preferential treatment. We estimate the effectiveness of this social procurement policy on a firm's training participation, training intensity, and training quality using information from a representative and large firm survey. The results show that although the policy increases the number of training firms, the effect is limited in size, as only small firms and firms operating in sectors where public procurement represents a large share of the business, are affected positively. As a robustness check we further exploit a natural variation in the incidence of public procurement policies across Cantons and apply a difference-indifferences strategy. The results from this robustness check lie within the range of the effect estimated exploiting the cross-sectional data. Furthermore, we find no evidence that firms offering training due of public procurement policies provide training of a below-average quality.
Keywords: H32; I28; J08; 330; apprenticeship training; difference-in-differences; matching; public procurement policy; social public procurement